Sedimentation properties of chitosomal chitin synthetase from the wild-type strain and the ‘slime’ variant of Neurospora crassa - Martínez, José P.; Giménez, Gloria; Bartnicki-García, Salomon (Biochimica et biophysica acta, 1989)
Marked differences in the pattern of sedimentation of cellular structures were observed after isopycnic centrifugation of crude cell-free preparations from the Neurospora crassa wall-less ‘slime’ variant and mycelial wild-type strain. Kinetic studies of particle sedimentation showed that the various types of subcellular components, as revealed by turbidity, UV absorption, polypeptide patterns, and chitin synthetase activity determinations, sediment independently of one another. An important feature was the finding that chitin synthetase from ‘slime’ peaked at a median specific gravity of 1.1201 ± 0.0036, whereas that from wild-type strain sedimented at a higher buoyant density (specific gravity 1.1349 ± 0.0024). Different cultivation conditions or cell breakage procedures (osmotic lysis or ballistic disruption) did not seem to affect this sedimentation behavior. Electron microscopy revealed the presence of chitosomes (microvesicles containing chitin synthetase) in the chitin synthetase activity peaks obtained after isopycnic centrifugation of cell-free extracts from 'slime' and wild-type strains. The discrepancy in buoyant density of chitin synthetases from both N. crassa strains might point to inherent differences in chemical composition of the chitosomal microvesicles. In any case, the lower buoyant density of ‘slime’ chitosomes appears to be one of several major alterations in sedimentation behavior of subcellular structures. These alterations might be related to the inability of ‘slime’ to make a cell wall.